Absorption spectroscopy of ethylene near 1.62 µm at high temperatures. (January 2020) - Zhang, Gang; Gao, Guangzhen; Zhang, Ting; Liu, Xin; Peng, Changde; Cai, Tingdong
Highlights: The high-resolution spectra of C2 H4 at 1.62 µm are acquired in the temperature range of 296–600 K. More than 50 lines are recorded in the frequency range 6167.39 to 6177.71 cm −1 . Line positions, line intensities, self-broadening coefficients and its temperature exponent n for those lines are determined by multi-line fitting using Voigt profile. Abstract: We report the measured line positions, line intensities, self-broadening coefficients and its temperature exponent n of C2 H4 for more than 50 lines in the frequency range 6167.39 to 6177.71 cm −1 . These spectroscopic parameters were determined by multi-line fitting using the Voigt profile of absorption spectra measured with a distributed-feedback (DFB) tunable diode laser in a well-controlled heated static absorption cell in a temperature range of 296–600 K. The key factors influencing the uncertainties in the determination of the line intensities and self-broadening coefficients were analyzed respectively. To the best of our knowledge, this is the first study that measures the spectrum of C2 H4 near 1.62 µm and the line parameters at elevated temperature.